Institutional Accessibility in Providing Development Data as a Primary Dimension of the Village Government's Public Accountability - Muhammad Taufiq; Rahmad Hidayat (Universitas Sultan Ageng Tirtayasa, 2024)
This essay examines the extent to which the village government is institutionally accessible in conveying development data to its citizens. Dervin (1973) defines institutional accessibility as the ability and willingness of public institutions to provide individuals with essential information. The easily accessible nature of such governmental entities would result in greater accountability and transparency in government administration, development, and community responsibility, which are constitutional obligations of state institutions. The authors describe the Rabakodo Village administration's level of public accountability in managing development operations, as evidenced by institutional accessibility to creating general information disclosure. This is a descriptive-qualitative study that uses focus group discussions and in-depth interviews as the primary methods of data collection. Public accountability may not have been fully implemented up to this point due to the lack of serious consideration given to the attempts to develop responsible village governance in Rabakodo Village. The lack of sincerity can be seen in the absence of adequate communication media to publicize the village development program while meeting the community's needs for information on specific development operations. The village government's failure to optimize the availability of different communication platforms and provide full access to village development information posed a barrier to increasing participatory democracy, inclusiveness, and public accountability. Such a low level of institutional accessibility steadily diminishes the possibility of confronting detrimental practices, non-populist policies, and the corrupt orientation of village-level state actors.